Pengaruh Kualitas Produk, Promosi dan Keragaman Produk Terhadap Keputusan Pembelian Pelanggan Indomaret Orchid Park 11 - Simanjuntak, Juntaris Parbisukan; Khoiri, M (Jurnal Disrupsi Bisnis, 2024)
This research aims to assess the influence of product quality, promotion and product diversity on the purchasing decisions of Indomaret Orchid Park 11 customers. The subjects used as the population for this study are individuals who purchased at Indomaret Orchid Park 11, Batam City in 2023, the exact number is not known, while the sample consisted of 204 respondents selected using the Jacob Cohen formula method drawn using purposive sampling. To analyze the data, the multiple linear regression method was used to test data quality, classical assumptions, influences and hypotheses. The results of multiple linear regression analysis show that product quality has an impact of 21.3% on purchasing decisions. Promotions have an impact of 31.6% on purchasing decisions. Product diversity has an impact of 29.7% on purchasing decisions. From the analysis of the coefficient of determination (R2), it can be concluded that the combination of product quality, promotion and product diversity can explain around 68.2% of the variation that occurs in purchasing decisions. In addition, the t test and F test show that product quality, promotion and product diversity partially or jointly have a positive and significant effect on Indomaret Orchid Park 11 customers' purchasing decisions.